Characterization and Comparison of Commercial Chinese Cereal and European Grape Vinegars Using 1H NMR Spectroscopy Combined with Multivariate Analysis. Issue 11 (24th October 2016) - Wang, Xiaohua; Wang, Jie; Kamal, Ghulam Mustafa; Jiang, Bin; Sun, Peng; Zhang, Xu; Liu, Maili
Abstract: A holistic and comparative quality assessment of vinegars from different countries is needed with international trade of vinegar become frequent. In this study, compounds characterization and comparison of commercial‐grade Chinese cereal and European grape vinegars were performed using 1 H NMR spectroscopy coupled with principal component analysis (PCA) and orthogonal projection to latent structures discriminate analysis (OPLS‐DA). The results showed that Balsamic vinegars of Modena were clearly discriminated by higher amount of fructose and glucose, while Chinese aromatic vinegar and aged vinegars were characterized by higher amount of amino acids, volatile compounds, succinate and betaine. On the other hand, flavoring compounds in Chinese rice vinegar and European wine vinegars are less than the others. These characteristic components are associated with the special raw materials and producing process of each types of vinegar and endow them special flavor. The results obtained in this study provide a global insight into vinegar through a 1 H NMR based compounds analysis that allows a holistic quality assessment and comparison of vinegars from different manufacture origins. Abstract : 1 H NMR based characterization and comparison are performed which allows a holistic quality assessment and comparison of Chinese cereal and European grape vinegar.